Childhood Sexual Abuse and Neglect as Predictors of Body Dysmorphic Symptoms among Gay Men - Ismawati Ismawati; Rr Dwi Astuti (Utan Kayu Publishing, 2026)
Body Dysmorphic Disorder (BDD) is increasingly recognized as a significant mental health condition associated with body image dissatisfaction and psychological distress. However, empirical research examining the impact of adverse childhood experiences, particularly among sexual minority populations, remains limited. This study aimed to examine whether childhood sexual abuse and child neglect predict body dysmorphic symptoms among gay men. It was hypothesized that both forms of childhood trauma would significantly contribute to body dysmorphic symptoms. This study employed a quantitative correlational design involving 202 participants recruited through purposive sampling. Standardized psychological instruments were used to assess body dysmorphic symptoms, childhood sexual abuse, and child neglect. Data were analyzed using Spearman correlation and multiple regression analysis. Results indicated that childhood sexual abuse was positively correlated with body dysmorphic symptoms (r = 0.185, p < 0.01), while child neglect showed a stronger correlation (r = 0.379, p < 0.01). Multiple regression analysis further demonstrated that both variables significantly predicted body dysmorphic symptoms (R = 0.460, p < 0.01), accounting for 21.2% of the variance. These findings emphasize the psychological impact of early adverse experiences on body image disturbances and highlight the importance of trauma-informed mental health interventions for sexual minority populations.